2008
DOI: 10.1556/oh.2008.28518
|View full text |Cite
|
Sign up to set email alerts
|

The role of osteocalcin in the connection of bone and glucose metabolism in humans

Abstract: This study confirmed the relationship between insulin sensitivity and osteocalcin in healthy human population, although basic difference was found between the two genders which was not related to osteocalcin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Another player in the hormonal regulation caused by spirulina would be osteocalcin. Osteocalcin, also stimulates pancreatic -cells to release more insulin, increasing insulin sensitivity [52][53][54][55][56]. Our data show that while osteocalcin levels decreased significantly in the control group over the experimental period, spirulina treatment significantly increased osteocalcin levels over time (p < 0.001); moreover, the increases were dose-dependent.…”
Section: Discussionmentioning
confidence: 56%
“…Another player in the hormonal regulation caused by spirulina would be osteocalcin. Osteocalcin, also stimulates pancreatic -cells to release more insulin, increasing insulin sensitivity [52][53][54][55][56]. Our data show that while osteocalcin levels decreased significantly in the control group over the experimental period, spirulina treatment significantly increased osteocalcin levels over time (p < 0.001); moreover, the increases were dose-dependent.…”
Section: Discussionmentioning
confidence: 56%
“…Recent studies in humans have also shown a relationship between OC and carbohydrate metabolism 5,6,16 . There is an association between OC and insulin sensitivity in healthy individuals 17 . Moreover, it has also been reported that OC is inversely related to fat mass and glucose in the elderly 5 and postmenopausal women 18 .…”
Section: Discussionmentioning
confidence: 97%
“…5,6,16 There is an association between OC and insulin sensitivity in healthy individuals. 17 Moreover, it has also been reported that OC is inversely related to fat mass and glucose in the elderly 5 and postmenopausal women. 18 Other studies have found that serum OC levels are negatively correlated with blood glucose levels, fat mass and markers of atherosclerosis such as brachial-ankle pulse wave velocity and thickness of the intima-media, and positively with total adiponectin in T2D.…”
Section: Discussionmentioning
confidence: 97%
“…The association between ucOC levels and glucose homeostasis is consistent and there is a large evidence reporting the role of ucOC as a regulator of glucose and energy metabolism 48,49 . Higher levels of this protein have been related to an improvement in insulin sensitivity and secretion due to the direct action of ucOC on adipocytes and β-cell mass 50 . As above mentioned, within a population of MetS patients, there are patients at higher risk than others to become diabetic patients depending on their metabolic profile.…”
Section: Discussionmentioning
confidence: 99%